Real-World Effectiveness of Nirmatrelvir/Ritonavir in Hospitalized Older Adults with Severe Omicron COVID-19: A Retrospective Cohort Study from China - Chen Y; Liu L; Liu Y; Huang F; Guo L; Wan W; Jiang H (Infection and Drug Resistance, 2025)
Yangxi Chen,1,2,* Lika Liu,1,* Yu Liu,1 Fang Huang,1 Lei Guo,1 Wenhui Wan,1 Haiyang Jiang1 1Department of Geriatrics, Jinling Hospital, Affiliated Hospital of Medical School, Nan Jing University, Nanjing, Jiangsu, 210002, People’s Republic of China; 2Department of Geriatrics, Affiliated Jinling Hospital, Southern Medical University, Nanjing, Jiangsu, 210002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenhui Wan, Email wanwhnj@sohu.com Haiyang Jiang, Email drjiang@hoboro.topBackground: The real-world effectiveness of Nirmatrelvir/ritonavir (NMV/RTV) against the SARS-CoV-2 Omicron variant in older patients remains uncertain. We aimed to estimate the effectiveness in older patients aged 80 and above with severe COVID-19.Methods: A retrospective study analyzed 263 COVID-19 patients aged 80 and above, admitted to the Department of Geriatrics at Jinling Hospital, affiliated with Nanjing University, between December 15, 2022, and January 15, 2023. Among them, 136 cases were non-severe, and 127 were severe. The severe cases were further categorized into a survival group (n=74) and a death group (n=53) based on 28-day mortality. Kaplan-Meier survival curves assessed 28-day survival, and Cox regression models identified factors influencing survival.Results: Among the 127 severe cases, the death group had significantly higher rates of stroke history, renal impairment, endotracheal intubation, renal replacement therapy (RRT), bacterial infection, but significantly lower rates of NMV/RTV use and anticoagulation (p< 0.05). Kaplan-Meier analysis indicated that NMV/RTV improved 28-day survival in severe older COVID-19 patients. Multivariate Cox regression identified NMV/RTV as a protective factor (adjusted hazard ratio [HR] 0.307, 95% confidence interval [CI] 0.152– 0.620, p=0.001), while COPD (adjusted HR 2.993, 95% CI 1.563– 5.731, p=0.001), stroke history (adjusted HR 3.871, 95% CI 1.953– 7.671, p< 0.001), and endotracheal intubation (adjusted HR 5.058, 95% CI 2.809– 9.108, p< 0.001) were significant risk factors for increased 28-day mortality.Conclusion: NMV/RTV may improve the 28-day survival rate of older patients aged 80 and above with severe COVID-19.Keywords: older adult, COVID-19, antiviral drugs, mortality